Una mirada al patrimonio cartaginés. La Casa Jiménez Sancho - Durán-Rodríguez, María Marta (2022)
This document provides the result of the actions developed by the Casa Jiménez-Sancho Pro-Restoration Commission between 2011and 2019 to make visible the importance of the building, its functionality, and recommendations for its use. The four phases of the restoration process and its current condition are documented. The information was gathered through documentary sources, interviews, photographs provided by members of the family and our own, work sessions of the established commission, plus the constant and close monitoring of the different stages of the intervention on the building. The house, its history, and its inhabitants were contextualized, thus allowing us to perceive not only its cultural, patrimonial, and architectural values but also its position in the Cartago imaginary.